THE INFLUENCE OF INFLUENCERS, DISCOUNTS, AND LIVE SHOPPING ON BRAND PURCHASE DECISIONS THE ORIGINOTE IN THE TIKTOK APPLICATION (STUDY PAD A FEB UNIVERSITY STUDENT MALIKUSSALEH) - Manhasa Hira Nur'Asyi AL Utary; Hamdiah; Ikramuddin; Heriyana (CV. Radja Publika, 2026)
This study aims to analyze the effects of influencers, discounts, and live shopping on purchasing decisions for the Originate brand on TikTok, focusing on female students of the Faculty of Economics and Business at Malikussaleh University. The background of this research is based on the rapid development of digital marketing through social media, particularly TikTok, which has evolved not only as an entertainment platform but also as an effective marketing medium influencing consumer behavior. This study employs a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to respondents who met the research criteria. The independent variables in this study are influencers, discounts, and live shopping, while the dependent variable is purchasing decisions. The results indicate that, partially, influencers, discounts, and live shopping do not have a significant effect on purchasing decisions. Furthermore, simultaneously, these three variables also do not significantly influence purchasing decisions for the Originate brand on TikTok. These findings suggest that purchasing decisions among female students are not solely influenced by these digital marketing strategies, but may also be influenced by other factors outside the research model. This study is expected to contribute to the development of digital marketing knowledge and serve as a reference for businesses in formulating more effective and targeted marketing strategies, especially in using social media as a promotional tool.